Residual effects of harvested and green-manured legumes on a subsequent barley crop in a subarctic environment - Sparrow, Stephen D.; Cochran, Verlan L.; Sparrow, Elena B. (Canadian Journal of Plant Science, 1995)
Experiments were conducted at two locations in Alaska to determine effects of incorporating and harvesting forage legumes on subsequent barley crops. Barley (Hordeum vulgare L.) following forage legume crops and fallow had higher yields and plant N than barley following non-N 2 -fixing crops. Incorporating, as opposed to harvesting, legume crops sometimes resulted in positive response of barley. Key words: Residual legume effects, green manure, Alaska, subarctic